A MECHANISTIC APPROACH FOR HEAT TRANSFER ESTIMATION IN HORIZONTAL NON-BOILING TWO-PHASE PIPE FLOW - C. Tang; A. Ghajar (Chemical Engineering Transactions, 2009)
Abstract preview not available - see full-text PDF article.